Comparisons of echo-integration performance from two multiplexed echosounders. (7th September 2018) - Macaulay, Gavin J; Scoulding, Ben; Ona, Egil; Fässler, Sascha M M
Abstract: A time-series of acoustically derived aquatic biomass estimates relies on the acoustic equipment maintaining the same performance throughout the time-series. This is normally achieved through a regular calibration process. When the acoustic equipment changes it is necessary to verify that the new equipment produces a similar result to the old equipment, otherwise an unknown bias can be introduced into the time-series. The commonly used Simrad EK60 echosounder has been superseded by the Simrad EK80 echosounder and the performance of these two scientific echosounder systems was compared using interleaved pinging through the same transducer. This was repeated for multiple transducer frequencies (18, 38, 70, 120, and 200 kHz) and from two vessels (Norway's G.O. Sars in the North Sea and The Netherlands' Tridens in the Northeast Atlantic Ocean). The broadband facility of the EK80 was not used. Regressions of the grid-integrated backscatter from the two systems were highly linear. The difference in area backscattering coefficients in typical survey conditions was less than 0.6 dB (12%) at the main survey frequency of 38 kHz. In most conventional fish acoustic surveys, the observed differences are less than other sources of survey bias and uncertainty.